Lifesaving for Beginners : - Edelstein, Anne (Book collections on Project MUSE., 2017)
"When Anne Edelstein was forty-two, her mother, a capable swimmer in good health, drowned while snorkeling in the Great Barrier Reef. Caring for two small children of her own, Anne suddenly found herself grieving not only for her emotionally distant mother but also for her beloved younger brother Danny, who had killed himself violently over a decade before. She finds herself wrestling not only with the past and her family's legacy of mental illness, but also with the emotional well-being of her children. Part memoir and part meditation on joy and grief, the book will resonate with anyone who has ever struggled to come to terms with their parents, their siblings, their children, and their place in the world"--Amazon.com.